2022
DOI: 10.1007/s10857-022-09547-2
|View full text |Cite
|
Sign up to set email alerts
|

High school mathematics teachers' changes in beliefs and knowledge during lesson study

Abstract: This research investigates how a lesson study (LS) on designing and implementing challenging tasks impacts Vietnamese high school mathematics teacher knowledge and beliefs. Its contribution highlights cultural considerations when adopting LS to the forefront to contextualize the impacts. The results show that the teachers developed their specialized content knowledge by attending to students’ mathematics and creating cognitive conflicts building on student responses. The teachers changed their curriculum knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Second, those LS studies that reported positive changes primarily emphasized the effects of LS on teachers’ changes in the personal/collective domain such as increased professional knowledge and more positive teaching attitudes and beliefs (e.g., Akiba et al, 2019; Corey et al, 2021; Leavy & Hourigan, 2016; Nguyen & Tran, 2022; Vermunt et al, 2019). However, there is little evidence that LS made a difference in the practice domain by shaping pedagogy or the external domain by influencing schools’ professional learning cultures and structures (Akiba & Wilkinson, 2016; Seleznyov, 2019; Willems & Van den Bossche, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Second, those LS studies that reported positive changes primarily emphasized the effects of LS on teachers’ changes in the personal/collective domain such as increased professional knowledge and more positive teaching attitudes and beliefs (e.g., Akiba et al, 2019; Corey et al, 2021; Leavy & Hourigan, 2016; Nguyen & Tran, 2022; Vermunt et al, 2019). However, there is little evidence that LS made a difference in the practice domain by shaping pedagogy or the external domain by influencing schools’ professional learning cultures and structures (Akiba & Wilkinson, 2016; Seleznyov, 2019; Willems & Van den Bossche, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The study highlighted that curriculum materials serve as a starting point for planning. In contrast, Nguyen and Tran (2022) found that teachers in their study play a role of curriculum makers as they develop more agency when planning learning for their students. In addition, when reflecting on their philosophy about important mathematics for their students, they consider the curriculum as only part of the resources that they need to draw on.…”
Section: Mathematics Teacher Planningmentioning
confidence: 88%
“…Teacher planning has shaped students' opportunities to learn (Amador & Lamberg, 2013) as evident when they choose educational tasks to address key ideas in learning. Also, this process is shaped by teachers' beliefs and understandings of mathematics teaching and learning (Drake & Sherin, 2006;Nguyen & Tran, 2022) and school context dependent (Superfine, 2008). For example, in the USA, teachers associate teacher guides with curriculum in planning, referred to as curriculum implementers (Superfine, 2008).…”
Section: Mathematics Teacher Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant feature is that LS occurs within the school environment, where teachers play a central role, and is based on teachers and researchers collaboration. LS creates a context for teachers' collective reflection and develops the sense of confidence that is central to teachers' professional development (Nguyen & Tran, 2022;Pang, 2016). In February 2020, the ICMI Study 25 Conference focused on Teachers of Mathematics working and learning in collaborative groups, and LS was very present in the presented research works (both in one plenary lecture and in 14 out of 80 accepted papers cited "Lesson Study" in the title, e.g.…”
Section: Introductionmentioning
confidence: 99%